PENGEMBANGAN PADI VARIETAS UNGGUL HIBRIDA: PENDEKATAN METODE QUALITY FUNCTION DEVELOPMENT DAN SENSITIVITY PRICE ANALYSIS - Firohmatillah, Agrivinie Rainy; Nurmalina, Rita (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2012)
One of the way to increase the rice production is the development of using hybrid paddy which is can increase 15-20 percent higher than inbrid rice production. This research was aimed at identifying customer wants and preferences of hybrid paddy attributes, applying Quality Function Deployment method in developing hybrid paddy, analyzing price sensitivity hybrid paddy seed at farm gate price. This research was conducted on April to May 2011. Primary data was collected from 30 costumers (rice field farmers that knows better to hybrid paddy and ciherang paddy the competitor) and four hybrid paddy breeders in Balai Besar Penelitian Padi. Quality Function Deployment and Price Sensitivity were applied to analyze the evidence. The results show that the quality of hybrid paddy is need more attention on some attributes. However, the first priority on attribute that should be improved to increase the quality of hybrid paddy is the productivity level.